Developing Digital Modules of Career Counselling for Students of Universitas Islam Raden Rahmat Malang - Titin Kholisna; Ridho Herasmara (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2020)
It is important for higher education institutions to put efforts on the competence achievement of their graduates in preparing their career. There needs to be mentoring to help students prepare for their career through career counselling service. Further, the existence of the latest technology helps manage life problems more systematically, practically, and efficiently. Therefore, a digital career counselling system in the format of a module can help ease the students’ career preparation flexibly. This research is aimed to produce career counselling digital modules for the students. It applied research and development method with quantitative and qualitative analysis to test the product. The data were obtained through focus group discussion and counselling with some experts chosen using cluster random sampling technique. The aim of career counselling is to investigate students’ self-understanding, career preparation and career readiness in relation to career selection. The analysis of product testing shows an average result of 3.5 of modules with the category good/suitable/interesting and appropriate. The digital application of career counselling helps students plan, prepare, and understand the discourse of career and the world of employment.